Kepatuhan penggunaan obat anti tuberkulosis fase intensif terhadap perubahan nilai sputum BTA dan berat badan di Puskesmas Bandarharjo Semarang - Farroh Bintang Sabiti; Nisa Febrinasari; Isfandiari Aulia (Sekolah Tinggi Ilmu Kesehatan Borneo Lestari Banjarbaru, 2021)
Tuberculosis disease requires a high degree of compliance, and a lack of treatment would result in the high failure rate of TB patients' medicine, so it would increase the risk of pain, death, and cause more and more resistant TB patients found with Basil Acid (BTA). This research is aimed at knowing drug adherence, BTA outcome and weight gain in intensive phase tuberculosis patients. At Bandarharjo Semarang. This is a kind of observational descriptive research. Compliance is done by method of pill count. The results of the research with 19 TB patients were in intensive phase with 17 obedient patients and 2 disobedient patients. The results of the BTA decision all respondents were negative in the second month, and all the respondents' weight increased. This research can be concluded that intensive phase tuberculosis patients at Puskesmas Bandarharjo have an average compliance of 91.8 ± 14.5, that is, 17 of the 19 respondents are deemed to be averaged by the Pill Count method. All respondents obtained negative BTA results and weight gain at the end of intensive phase.